Digital Financial Literacy and Digital Financial Inclusion in the Era of Digital Disruption: Systematic Literature Review - Desy Wulan Ayuning Gumilar; Khresna Bayu Sangka; Salman Alfarisy Totalia (PT FORMOSA CENDEKIA GLOBAL, 2024)
Financial technology in the era of digital disruption has transformed traditional mechanisms of financial services into more efficient. Digital financial literacy has become one of the important digital competencies in order to financial inclusiveness with technology. This article aim to explore publications related to digital financial literacy and digital financial inclusion and their impact regarding economic inequality and financial well-being.This article uses the method of systematic literature review with databases from Scopus from 2020-2024.The results found that digital financial literacy is needed to achieve optimization of digital financial inclusion; adoption of digital financial services has the potential to reduce economic and social disparities; digital financial inclusion can encourage increased financial well-being.The expansion of financial services with technology increases the coverage dimension but there are still barriers in the usage dimension.